Running Patterns in LaLiga Before and After Suspension of the Competition Due to COVID-19 - Brito de Souza, Diego; López-Del Campo, Roberto; Resta, Ricardo; Moreno-Perez, Victor; Del Coso, Juan (Frontiers in Physiology, 2021)
In the first wave of the COVID-19 outbreak (spring 2020), the first division of professional football in Spain (LaLiga) was suspended for 12 weeks as part of the lockdown imposed by the Spanish health authorities. Professional football players were confined to home for 8 weeks and then a retraining period of 4 weeks was set before the first competitive match. When competition was resumed, professional football teams competed in a congested calendar (11 matchdays in 39 days) while some in-game regulations were altered. The current investigation presents an analysis of running patterns before suspension and after resumption of LaLiga to determine how the lockdown affected players’ physical performance. A pairwise comparison was performed of running patterns of the 2019-2020 vs. 2018-2019 season. Using a two-way ANOVA (seasonxmatchday), it was found that there was no main effect of the season on total running distance per match (P=0.288) nor in the distances covered <14.0 km/h (P=0.294), at 21.0-23.9 km/h (P=0.266), and at ≥24.0 km/h (P=0.112). Only the distance at 14.0—20.9 km/h was affected by the season (P=0.019) with a lower running distance on matchday 34 in the 2019-2020 vs. 2018-2019 season. The number of substitutions (from 2.9 to 4.5 substitutions per game; P<0.001) and match duration (96 vs. 100 min; P<0.001) significantly increased after resumption respect to the previous season. These data suggest that running performance of professional football teams was maintained after the resumption of the competition while the alterations in the in-game regulations facilitated the maintenance of football physical performance.